A scale to measure the attitude towards improved fish processing methods - Kandoran, M.K., Thiagarajan, R. Mohan, B. and (Fishery Technology, 2021)
An attitude scale was constructed to measure the attitude of fisherwomen towards improved fish processing methods. To construct the attitude scale, 'scale' and ‘Q’ values (the interquartile ranges) were calculated for 31 statements selected, based on the opinion of 34 judges. Based on the 'scale' and ‘Q’ values 16 statements were selected with eight favorable statements and eight unfavorable statements. The weightages given were 3, 2 and 1 for favorable statements and 1, 2 and 3 for unfavorable statements.